A CASE OF NEUROFIBROMATOSIS TYPE 1 - Valentina Dimitrova; Ivelina Yordanova; Verka Pavlova; Valentin Valtchev; Dimitar Gospodinov; Boryana Parashkevova; Chavdar Balabanov (Peytchinski Publishing, 2008)
Neurofibromatosis (NF) is a term that has been applied to a variety of related syndromes, characterized by neuroectodermal tumors arising within multiple organs and autosomal-dominant inheritance. Neurofibromatosis type I (NF-1), known as well as Recklinghausen's disease, is the most common type of the disease accounting 90% of the cases. We present a case of 52-year-old men with NF-1. The disease started in childhood with the appearance of multiple hyperpigmented skin macules. At the age of 46 a lot of cutaneous tumors appeared and started growing bigger all over the body surface. Because of a vision problem due to an upper left eyelid neurofibroma, the patient came for a clinical examination at the age of 52 years.